An optical fiber hydrogen sensor using a palladium-coated ball lens - Chowdhury, Sahar A.; Correia, Ricardo N.; Francis, Daniel; Brooks, Simon J.; Jones, Benjamin J. S.; Thompson, Alexander W. J.; Hodgkinson, Jane; Tatam, Ralph P. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
A self-referenced optical fiber refractometer using a ball lens as a sensor head has been developed and characterized. A 350-μm ball lens created at the tip of a single mode fiber has been coated with a 40-nm optically thin layer of palladium that reacts with hydrogen to form a hydride, which has a lower reflectivity than pure palladium. Optical reflectance measurements from the tip of the ball lens were performed to determine the hydrogen response. The change in reflectivity is proportional to the hydrogen concentration in the range 0% to 1% hydrogen in air with a detection limit down to 10 ppm (1σ) in air. This technique offers a simple sensor head arrangement, with a larger sampling area (~40 times) than a typical single-mode fiber core. A statistical image analysis of a palladium film, with cracks created by accelerated failure, confirms that the anticipated sensor area for a ball lens sensor head has a more predictable reflectivity than that of a bare fiber core.
Keywords: Hydrogen; Hydrogen instrumentation; Optical fiber application; Palladium; Refractive index; Refractometer; Sensor